Wind Turbine Tower Modeling and Vibration Control Under Different Types of Loads Using Ant Colony Optimized PID Controller - Rahman, Mahmudur; Ong, Zhi Chao; Chong, Wen Tong; Julai, Sabariah; Ng, Xiong Wei (Springer, 2019)
Vibration in the wind turbine tower disturbs the reliability and increases the possibility of structural damage. Design and optimization of vibration controller are a key goal for wind turbine tower to achieve optimal performance. In this study, a proportional integral derivative (PID) is designed and optimized using nature technology to find optimal required force for actuators and therefore, reducing wind turbine tower vibration. PID controller parameters are optimized with ant colony optimization (ACO) and compared with traditional tuning methods such as Ziegler–Nichols and Tyreus–Luyben methods to ensure its effectiveness in minimizing wind turbine tower vibration. The optimized active vibration controller shows better performance than traditional method in terms of vibration reduction rate, ability to adapt when frequency varies and computational time. This paper also investigated finite difference method for wind turbine tower modeling, and its efficacy is compared with another well-known numerical finite element method based on mean squared error, fit to estimated data and cross signature assurance criterion. The performance of ACO optimized PID controller is investigated for wind turbine tower under four different types of disturbances and compared with uncontrolled and passive controlled system. Results show that 98, 84, 92 and 98% of displacement of the tower are reduced under simulated blade/rotor imbalance, impact, wind and turbulence disturbances, respectively, using ACO optimized PID controller. © 2018, King Fahd University of Petroleum & Minerals.